Cu Electrodeposition on Nanostructured MoS2 and WS2 and Implications for HER Active Site Determination. Issue 11 (23rd July 2020) - Wu, Longfei; Dzade, Nelson Y.; Chen, Ning; van Dijk, Bas; Balasubramanyam, Shashank; Sharma, Akhil; Gao, Lu; Hetterscheid, Dennis G. H.; Hensen, Emiel J. M.; Bol, Ageeth A.; De Leeuw, Nora H.; Hofmann, Jan P.
Abstract : Cu electrodeposition in both underpotential and overpotential regimes on nanostructured MoS2 and WS2 prepared by plasma-enhanced atomic layer deposition has been studied in detail. A combination of electrochemical methods, advanced characterization by X-ray absorption spectroscopy (XAS) as well as theoretical modelling were employed to reveal Cu adsorption modes on transition metal dichalcogenides (TMDs) from initial stages until bulk deposition. Since Cu UPD on TMDs has been used recently to evaluate the number of electrochemically active sites ( N AS ) for H2 evolution reaction, we evaluate and discuss here the implications of the Cu electrodeposition phenomena on nanostructured MoS2 and WS2 gauging the general applicability of the Cu UPD method for number of HER active sites determination in TMDs. Although an apparently better correlation of HER current density with Cu UPD charge than with double layer capacitance is found, the Cu UPD method cannot be used quantitatively because of the absence of a clear H UPD phenomenon on the studied nanostructured TMDs. This is in contrast to platinum group metal catalysts where H UPD and Cu UPD sites are strongly correlated.